Chronic Mucocutaneous Candidiasis in Early Life: Insights Into Immune Mechanisms and Novel Targeted Therapies - Shamriz, Oded; Tal, Yuval; Talmon, Aviv; Nahum, Amit (Frontiers in Immunology, 2020)
Children with chronic mucocutaneous candidiasis (CMC) experience recurrent infections with Candida spp. Moreover, immune dysregulation in the early life of these patients induces various autoimmune diseases and affects normal growth and development. The adaptive and innate immune system components play a significant role in anti-fungal response. This response is mediated through IL-17 production by T helper cells. Inborn errors in IL-17-mediated pathways or Candida sensing molecules are known to cause CMC. In this review, we describe underlying immune mechanisms of monogenic primary immune deficiency disorders known to cause CMC. We will explore insights into current management of these patients and novel available therapies.